Pengaruh Penggunaan Aplikasi Lectora Inspire terhadap Ranah Kognitif dan Minat Belajar Peserta Didik - Dewi Rachmawati; Laelia Nurpratiwiningsih; Dedi Romli Triputra (Peneliti.net, 2022)
This study aims to determine the effect of using the Letora Inspire application on learning outcomes in the cognitive domain and student interest in learning. This research is motivated by the problems found in the field, namely the low learning outcomes in the cognitive domain and interest in learning mathematics subjects. It is proven from the PTS result document of students. This type of research is a quantitative experiment with a posttest-only group design. The data collection technique used to determine the aspects of using the Lectora Inspire application was using a questionnaire, cognitive domain assessment using a test assessment sheet and an assessment of learning interest using a questionnaire. The pollution used in this study were all fourth grade students of SD N 01 Kalimati, totaling 43 students. The sample used is the saturated sample in this study, namely class IVA (control class) and class IV B (experimental class). Data collection techniques in the form of post-test questions, learning interest questionnaires and questionnaires on the use of the Lectora Inspire application. The final data analysis used is the t test. The results obtained are: (1) X test against Y1 obtained a significant value of 0.002 <0.05; so that there is an influence between the interactive learning media of the Lectora Inspire application on the learning outcomes of the cognitive domain of students. (2) X test against Y2 obtained a significant value of 0.005 <0.05; so that there is an influence between the interactive learning media of the Lectora Inspire application on the learning interest of students